HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI USIA 6 BULAN DI PUSKESMAS TEMBOKREJO KECAMATAN GUMUKMAS KABUPATEN JEMBER - Elfira Nurul Aini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2013)
Exclusive breastfeeding is breastfeeding without any additional food and drink in infants aged zero to six months. Success in infant nutrition is indicated by weight and height to reflect the nutritional status of infants. After a preliminary study in 23 infants in health centers known Tembokrejo 34.5% infants receive only breast milk with the details of the nutritional status of the nutritional status of more than 60%, 40% good nutritional status, malnutrition 0%, 0% BGM. The study was a descriptive cross sectional correlation method. Stratisfied sampling using random sampling, which of the 38 infants aged 6 months, 12 babies are not exclusively breast-fed and 26 exclusively breastfed infants. Measuring instruments used to collect data were questionnaires and systematic observation (KMS). The data obtained is then tabulated and analyzed with Sommes'd test that has an error rate of α = 5% (0.05). The results obtained in infants who are exclusively breast-fed babies have gi 50% more and 50% good nutrition, while in infants who are not exclusively breast-fed 33.3% and 58.3% more nutrient malnutrition. Having analyzed the resulting count equal to -0.077 Z is smaller than the critical value of 1.96. There was no association between exclusive breastfeeding and nutritional status of infants aged 6 months. However, given the benefits, the researchers recommend to stick exclusively breastfed infants.